Berpikir Aljabar Siswa dalam Menyelesaikan Masalah Tebak Bilangan Menggunakan Microsoft Excel - Adelia, Dhynda; Rosyidi, Abdul Haris (Universitas Negeri Surabaya, 2025)
This study aims to describe students' algebraic thinking in solving number guessing problems using Microsoft Excel. In human life, algebraic thinking plays a very important role. Many problems in human life can be solved with algebraic thinking. In solving mathematical problems, Microsoft Excel can be used to assist students in solving mathematical problems. The method used in this study is qualitative, involving junior high school students as research subjects. The subjects are divided into two categories: the first category consists of students with correct mathematical modeling and correct Microsoft Excel formulas, and the second category consists of students with correct mathematical modeling but incorrect Microsoft Excel formulas. Data were collected through analysis of students' work completed using Microsoft Excel and interviews. he results of the study show that the difference in students' algebraic thinking between those with correct formulas and those with incorrect Microsoft Excel formulas is evident in the processes of organization, analytical thinking, and generalization. Students with correct Microsoft Excel formulas can solve equations easily, while students with incorrect Microsoft Excel formulas solve equations without paying attention to the order of operations. In the generalization process, students with correct Microsoft Excel formulas create formulas without the aid of solving equations, whereas students with incorrect Microsoft Excel formulas create formulas by combining operations in solving equations. The formulas created do not use parentheses, causing the Microsoft Excel system to perform multiplication and division operations first. These findings suggest that when using Microsoft Excel in lessons, attention should be paid to the use of punctuation marks that can affect the order of operations in the Microsoft Excel system.